Sebuah Penerapan Barang Parasut Sebagai Alternatif Distribusi Logistik Untuk Membantu Korban Bencana Alam Di Daerah Terisolir - Ariesetyadi, Mahardhani Wahyu; Khaerudin , Khaerudin; Ade Muhammad; Purnama Sari (CV. AFDIFAL MAJU BERKAH, 2024)
Facing the complexity of logistics distribution related to natural disasters in Indonesia, a geographically vulnerable country to various types of disasters, especially in isolated areas, requires an efficient and effective solution. One solution being explored is the implementation of cargo parachutes as an alternative logistics distribution to enhance the resilience of communities in those areas. This research aims to provide an in-depth understanding of the potential and challenges of using cargo parachutes in the context of logistics distribution in Indonesia. Through a literature review conducted using the Systematic Literature Review (SLR) method, this study explores information regarding the advantages, challenges, and practical implications of implementing cargo parachutes. It was found that the use of cargo parachutes offers a quick and responsive solution in distributing logistics aid in isolated areas, often difficult to reach by conventional land transportation. The main advantage of implementing cargo parachutes is their ability to provide faster response times in logistics distribution. In the context of natural disasters, speed is crucial to ensure that aid arrives promptly where it is needed. Cargo parachutes can also improve the accessibility of aid, especially in isolated areas that may be challenging to reach conventionally. However, this study also identifies several challenges that need to be addressed. Landing accuracy is a critical issue, especially with weather variability, wind direction, and the topography of the area. Additionally, safety aspects, operational costs, and coordination among various stakeholders are challenges that must be overcome to ensure the success of cargo parachute implementation. Practical recommendations emerging from this research involve the use of monitoring technology, training for personnel involved in logistics distribution using cargo parachutes, and the development of clear Emergency Standard Operating Procedures (SOP). Monitoring technology, such as GPS, can help improve landing accuracy, while personnel training and emergency SOPs can enhance operational effectiveness and safety.